Wooden homeowners attitude and preferences for timber as a building material at Bachok, Kelantan - Abdul Manaf, Nurul Najihah (2018)
Malaysia is a timber-rich country but the use of timber products in construction industry are still lacking. There are many reasons that make Malaysian not really interested in timber as building material. This include because of poor and inconsistent quality of timber, association with low social status of citizen, as well as high cost of material. Even that timber may be more environmentally sustainable building material, the perception of homeowners and consumer may not really match with reality. This study was carried out to determine attitude of wooden homeowners towards timber as building materials and to know the preferences of wooden homeowners towards timber as building materials. A total of 288 respondents who’s staying in Bachok, Kelantan participated in this research of which 132 were males and 156 are females. Based on the findings, most wooden homeowners have positive attitude towards timbers as building materials but on preferences they have preferred to choose non-wooden house compared to wooden house. In terms of attitudes, they have a negative attitude towards the characteristics of timber such cheaper wood prices, the application is unlimited and not easily attacked by insects or insects. Thus, it make their preferences from timber material shifted to non-timber material such concrete, brick, cement and others. On preferences, most of respondent not preferring timber because the stable and durability of non –timber, material price of timber are expensive, non-wooden house is more unique and attractive then the lack of skilled manpower or carpenter of wooden house. Professionals in the construction industry will need to constantly update new technology or knowledge in wood to upgrade the quality of wood as a building material. In addition, timber sector needs to be promoted to educate people about the quality, maintenance and durability of timber as material in construction.